tera optimisation of azep low carbon cycle. - Hameed, Rukayat Opeyemi (Cranfield University, 2015)
Climate change represents one of the single most challenging problems facing the world today. According to the National Oceanic and Administrative Association, atmospheric temperature rose almost 25% since 1958, Artic sea ice has shrunk 40% since 1959 and global sea levels have risen more than 5.5 cm since 1990. According to the recent report released by the IPCC, the global mean concentration of carbon dioxide in the atmosphere is now 400ppm, 50 ppm above the proposed safe level. In this project, Techno economic, emissions and risk analysis of four simple and combined configurations of the advanced zero emission power plant was examined. The major difference between the advanced zero emission power plant and the conventional gas turbine is that the gas turbine combustor is replaced with the mixed conductive membrane reactor in AZEP. The AZEP drew a lot of attention because its ability to capture ~100% CO₂ and also boasts of about 30-50% cost reduction compared to other carbon abatement technologies, the penalty in efficiency is also not as much as its counterparts and has almost zero NOx emissions due to very low nitrogen concentrations in the working fluid. The AZEP cycle performance module was developed using the FORTRAN 95 software, single and dual pressure Bottoming cycle/Rankine cycle was conducted using a model built with Mathworks Matlab, economic and emission analysis was conducted using Microsoft office Excel and Mathworks Matlab and @RISK software was used for risk analysis followed by optimization case study which was conducted using Genetic algorithm MATLAB model. In the study, two major changes was made to the simple AZEP cycle to improve efficiency and power output, addition of either pre-expansion reheater or flue gas turbine or both. The study concluded that addition of reheater reduces thermal efficiency and increases capital cost compared to the addition of flue gas turbine. From the analysis conducted, AZEP cycle Configuration D had the highest efficiency and power output for both simple and combine cycle. Configuration D combined cycle also had the lowest LCOE and highest net present value. However, the technology readiness level for Configuration D is lower compared to Configuration C, therefore, optimization case study was conducted for Configuration C with objective function of minimizing emission and minimizing levelized cost electricity. The study found that use of optimizer could help reduce cost and emission significantly during the operation of the power plant. In addition, the cycles cost metrics were measured with and without enhance oil recovery income. The study found that income from enhanced oil recovery could reduce the levelized cost of electricity by approximately £9/MWh which could cover the CO₂ transportation cost. This research work concluded that the use of membrane technology could significantly reduce the CO₂ capture cost of natural gas power plant and will play an important role in cost reduction and penalty reduction in implementation of the carbon capture and storage technology.
Keywords: Membrane; greenhouse gas; optimization; emissions; CCS; AZEP